2014
DOI: 10.1155/2014/570894
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of IL-17A Might Suppress the Th1 Response and Promote the Th2 Response by Boosting the Function of Treg Cells during Silica-Induced Inflammatory ResponseIn Vitro

Abstract: Silica inhalation can induce chronic lung inflammation and fibrosis. Upon silica stimulation, activated macrophages trigger the T-lymphocyte which can differentiate into many different types of Th cells, including the recently discovered Th17 cells. IL-17A, the typical Th17 cytokine, is reported in some inflammatory diseases. However, the role of IL-17A in silica-induced inflammatory response is still not clear. The regulatory mechanism of silica-induced Th17 response also needs to be investigated. So we estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Cell treatment C57BL/6 mice were randomly allocated into 2 groups according to weight: antiCD22 group and vehicle group as needed. Macrophages were isolated from vehicle group mice intraperitoneally, and puri ed by a 2 hrs adherence culture as previous described [26]. CD4 + T cells were rst puri ed from vehicle group mice spleen by MACS, and then Treg(CD4 + CD25 + ) and Teff (CD4 + CD25 − )were separately isolated by positive selection and negative selection according to a magnetic column-based system Treg/Teff cell isolation kit (Miltenyi Biotech, Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Cell treatment C57BL/6 mice were randomly allocated into 2 groups according to weight: antiCD22 group and vehicle group as needed. Macrophages were isolated from vehicle group mice intraperitoneally, and puri ed by a 2 hrs adherence culture as previous described [26]. CD4 + T cells were rst puri ed from vehicle group mice spleen by MACS, and then Treg(CD4 + CD25 + ) and Teff (CD4 + CD25 − )were separately isolated by positive selection and negative selection according to a magnetic column-based system Treg/Teff cell isolation kit (Miltenyi Biotech, Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The Th17 response also is involved in the initial stage of silicosis. IL-17 neutralization can influence the traditional Th1/Th2 immune balance after silica instillation 4 5 6 . We previously demonstrated that CD4 + Foxp3 + Treg was involved in modulation of Th immune balance after silica instillation.…”
mentioning
confidence: 99%
“…In addition, significant changes in CD3 + count and ratio of CD4 + / CD8 + change in spleen were observed during viral infection Tang et al, 2014;Yang et al, 2013). We found that H1N1 inhibit the generation of CD3 + T cells and disturb the differentiation of T-lymphocyte subsets (Fig.…”
Section: However Intraperitoneal Administration Didn't Work (Data Nomentioning
confidence: 62%